Dehanding in Improving Fruit Quality of Banana - Sarkar, S. (International Journal of Bio-resource and Stress Management, 2015)
The experiment was conducted at the Horticultural Research Station, Mondouri, Bidhan Chandra Krishi Viswavidyalaya, West Bengal, India during the years 2007-2010 to assess the effect of dehanding on physico-chemical properties and quality of banana (Musa AAA Cv. Grande Naine). Accordingly terminal/distal hand (s) were removed in 3 (three) different intensity viz., i) removal of 1 (one) hand, ii) removal of 2 (two) hands and iii) removal of 3 (three) hands at various time after bunch emergence i.e, i) immediately after opening of last hand, ii) one week after opening of last hand, iii) two weeks after opening of last hand and iv) three weeks after opening of last hand. In general, dehanding decreased bunch weight over control and the intensity of reduction increased with delayed dehanding after opening of last hand. But removal of three hands immediately after opening of last hand increased fruit weight, fruit length, fruit circumference and pulp weight to the maximum tune of 53.9, 34.5, 13.9 and 58.6% respectively over the control. Unlike fruit morphological characters, the biochemical composition of fruits was not influenced significantly by dehanding except with reducing sugar. Dehanding also shortened the crop cycle by 18 days. The results signified the relevance of dehanding in improving market appeal and customer attraction of banana.